Consultative Meetings of the Heads of States of Central Asia: Analyzing the Prospects of Regionalism and Cooperation in Central Asia - Umirzakova, N.; Marat, T. (International School of Economics Maqsut Narikbayev University, Astana, 2024)
The high level of disintegration in Central Asia has become the focus of copious amounts of scholarly works on the region. However, the Consultative Meetings of Central Asian Leaders held from 2018 to 2023 became an occasion to reconsider the discourse around the future of regionalism in Central Asia. Due to the recentness of the informal meetings of the heads of the five Central Asian countries, this topic has not yet received a sufficient level of attention from the scientific community, which is why the value, influence and implications for the long-term future of the area of these meetings remain undisclosed. This study analyzed the content of the speeches of each of the Presidents of the countries who spoke at the fourth and fifth consultative meetings using qualitative methods, namely Critical Discourse Analysis techniques to gather information, considering linguistic constructions and the emotional narrative of the leaders concerning cooperation in the region to answer the main question and understand whether the discourse of cooperation or a deep-level integration prevails among the visions of Central Asian leaders concerning the future direction for the area. Moreover, for a deeper analysis of regionalism in Central Asia, the literary review will examine the previous works of such scholars on Central Asia as Ikboljon Qoraboaev, Filippo Costa Buranelli, Nargis Kasenova and others to delve into the current discourse on regionalism in CA. This study has a huge significance and relevance because the intentions of the Presidents of the region and, accordingly, its future remain unclear and vague for the scholarly community and interested parties, thereby there is a need to fill the gap concerning the role of recent meetings of leaders for affairs’ dynamics in the region. During the study, it was concluded that the vast majority of speeches by the Presidents of the Central Asian countries indicate a desire to maintain cooperation without a straightforward initiative to increase the level of integration, however, some projects proposed at the summit still suggest the idea of a possible rapprochement of countries in the political, economic and cultural levels.
Keywords: Consultative Meetings of the Heads of States of Central Asia, Russia on regionalism in Central Asia, regionalism in Central Asia, Turkey on regionalism in Central Asia…………………………….21